2021
DOI: 10.3389/fmicb.2020.575255
|View full text |Cite|
|
Sign up to set email alerts
|

Direct Evidence of Abortive Lytic Infection-Mediated Establishment of Epstein-Barr Virus Latency During B-Cell Infection

Abstract: Viral infection induces dynamic changes in transcriptional profiles. Virus-induced and antiviral responses are intertwined during the infection. Epstein-Barr virus (EBV) is a human gammaherpesvirus that provides a model of herpesvirus latency. To measure the transcriptome changes during the establishment of EBV latency, we infected EBV-negative Akata cells with EBV-EGFP and performed transcriptome sequencing (RNA-seq) at 0, 2, 4, 7, 10, and 14 days after infection. We found transient downregulation of mitotic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…Our analysis of the fully EBV-immortalized LCL GM12878 indicated that unannotated splicing in this cell line was comparable to that of activated, differentiated B cells in vivo (Figure 1). To investigate the stage at which the unique splicing pattern of blood NBCs is reversed, we obtained RNA-Seq datasets from timecourse experiments of EBV infection leading to LCL establishment (17)(18)(19)(20). Consistent with previously observed similarities between in vitro EBV-associated activation and in vivo antigen-mediated activation (16,17), fully EBV-immortalized LCLs from two different laboratories showed strong enrichment in the expression of genes associated with PCs relative to their parental blood B cells (Figure 2A).…”
Section: Splicing Changes Are Early Events In B Cell Differentiationsupporting
confidence: 69%
“…Our analysis of the fully EBV-immortalized LCL GM12878 indicated that unannotated splicing in this cell line was comparable to that of activated, differentiated B cells in vivo (Figure 1). To investigate the stage at which the unique splicing pattern of blood NBCs is reversed, we obtained RNA-Seq datasets from timecourse experiments of EBV infection leading to LCL establishment (17)(18)(19)(20). Consistent with previously observed similarities between in vitro EBV-associated activation and in vivo antigen-mediated activation (16,17), fully EBV-immortalized LCLs from two different laboratories showed strong enrichment in the expression of genes associated with PCs relative to their parental blood B cells (Figure 2A).…”
Section: Splicing Changes Are Early Events In B Cell Differentiationsupporting
confidence: 69%
“…DDR is also temporarily induced and attenuated until latency is established [ 106 ]. However, unlike lytic replication, cellular DNA synthesis and cell division occur several days after primary infection, progeny viruses are not produced, and BZLF1 is not necessary for infection during the pre-latent phase [ 107 , 108 ]. Thus, because cellular aspects during the pre-latent phase differ from those of the lytic phase, little is known about how viral DNAs are synthesized, including whether RCs are formed, although viral DNA is abundantly amplified during the pre-latent phase.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recently it has been suggested that cells during the “abortive lytic phase” exist [ 109 ]. The “abortive lytic phase” is, so to speak, an “incomplete lytic cycle”, wherein several early lytic genes are expressed without progeny viral production like the pre-latent phase [ 108 , 110 ]. Studying these “incomplete lytic phases”, including whether RCs are assembled or not, might unveil the novel significance of RC formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been commonly acknowledged that EBV + tumors are largely composed of latently infected cells, accumulating evidence has shown a remarkable role of EBV lytic gene products in EBV-driven oncogenesis [ 1 , 89 , 90 ]. While a number of EBV lytic genes have been found to be expressed in a “leaky” fashion during the early stage of EBV infection, a very limited number of infectious virions were detected shortly after EBV entry into B cells, with reactivation usually not occurring for two weeks thereafter [ 91 , 92 , 93 ]. An abortive (incomplete) lytic replication cycle in the pre-latent stage is suggested as a first phase during the development of the EBV infection within the host [ 1 , 91 , 94 , 95 ].…”
Section: Role Of Lytic Replication For Ebv Infection Immune Control and Oncogenesismentioning
confidence: 99%
“…While a number of EBV lytic genes have been found to be expressed in a “leaky” fashion during the early stage of EBV infection, a very limited number of infectious virions were detected shortly after EBV entry into B cells, with reactivation usually not occurring for two weeks thereafter [ 91 , 92 , 93 ]. An abortive (incomplete) lytic replication cycle in the pre-latent stage is suggested as a first phase during the development of the EBV infection within the host [ 1 , 91 , 94 , 95 ]. This implies that the transient lytic gene expression may play a supportive role during latency development, tumor formation, and LCL generation.…”
Section: Role Of Lytic Replication For Ebv Infection Immune Control and Oncogenesismentioning
confidence: 99%